The Impact of Demographic Dynamics on Household Saving in Pre-COVID-19 South Africa - Afamefuna Emmanuel Nwogbo; Joel Hinaunye Eita; Sivan Chetty (Managing Global Transitions, 2025)
This paper examines the effect of demographic dynamics on household saving in pre-COVID-19 South Africa, across all nine provinces of South Africa. The study used panel autoregressive distributed lag (PARDL) and Dumitrescu-Hurlin panel causality methods. The results revealed a longrun relationship between demographic dynamics and household saving in South Africa, showing that the White working age population had a significant effect on South Africa’s household saving in both the long-run and short-run, while the Black and Coloured working age population groups significantly impacted household saving only in the long-run. However, the Asian/Indian working age population had no effect on household saving in either the long run or short run. The Dumitrescu-Hurlin panel causality analysis revealed a bidirectional causality running between Asian/Indian, Black, and Coloured population groups and household saving, while a unidirectional causality was found running from the White population group to household saving.